Math, asked by akkujsr12, 6 months ago

4 -2(z-4)/3=1/2(2z+5)​

Attachments:

Answers

Answered by muskanperween225
4

Step-by-step explanation:

4 -  \frac{2(z - 4)}{3}  =  \frac{1}{2} (2z + 5)

4 -  \frac{2z - 8}{3}  =   \frac{2z + 5}{2}

4 -  \frac{2z - 8}{3}  -  \frac{2z + 5}{2}  = 0

 \frac{24 - 2(2z - 8) - 3(2z + 5)}{6}  = 0

 24 - 4z + 16 - 6z - 15 = 0

 - 10z + 24 + 1 = 0

 - 10z + 25 = 0

 - 10z =  - 25

z =  \frac{25}{10}

z = 2.5

Answered by sajeev157
1

ANS:Z=5/2

Step-by-step explanation:

HOPE IT HELP YOU

Similar questions